Impact of mannoproteins from different yeast species on wine properties - Carla Snyman; Julie Mekoue Nguela; Nathalie Sieczkowski; Matteo Marangon; Benoit Divol (OENO One, 2023)
The extent to which the addition of extracted mannoproteins (MPs) improve wine properties such as mouthfeel, clarity and colour stability is a controversial topic, and conflicting results have been reported. One possible explanation for this is the diversity that exists between MPs, a prevalent cause for which is their yeast strain of origin. However, although wine yeast species other than Saccharomyces cerevisiae possibly present an untapped source of MPs, their influence on wine as extracted additives is still ill-characterised. This study sought to compare the impact of MPs extracted and purified from different yeast species, named Saccharomyces boulardii, Saccharomyces cerevisiae, Metschnikowia fructicola and Torulaspora delbrueckii, as well as a commercial control, on wine. MPs were applied to a red and a white wine at three different concentrations, and BSA-reactive tannins, polymeric pigments, colour characteristics, browning potential and protein haze-forming potential were measured over the course of six months. The most notable differences were observed for the commercial MP, which achieved lower BSA-reactive tannins, increased polymeric pigments and a greater reduction of browning potential. This could be due to the difference in preparation procedures compared to the MPs extracted and purified for this study, possibly leading to variations in the commercial MPs’ structure and composition. However, some differences were also evident between species, with M. fructicola treatments achieving a 20 % reduction in browning compared to ~10 % for the other purified MPs and significantly increased colour intensity of red wine treated with low concentrations of T. delbrueckii. This study highlights alternative yeast species as a potential source of MPs with diverse benefits to wine and the need for further investigation into their diversity and properties to promote their eventual exploitation.